Sharing personal health record data elements in protective custody: youth and stakeholder perspectives. (31st July 2019) - Dexheimer, Judith W; Greiner, Mary V; Beal, Sarah J; Johnson, Darius; Kachelmeyer, Andrea; Vaughn, Lisa M
Abstract: Objective: The study sought to develop the necessary elements for a personalized health record (PHR) for youth emancipating from child protective custody (eg, foster care) by collecting thoughts and ideas from current and former foster youth and community stakeholders who have a significant amount of experience working with emancipating young people. Materials and Methods: We employed a mixed methods, participatory research design using concept mapping to identify key features for PHR across stakeholders. Results: In the clusters, common themes for necessary elements for a PHR included health education, health tips, medication instructions, diagnoses including severity, and website resources that could be trusted to provide reliable information, and addressed data privacy issues such as the primary user being able to choose what diagnoses to share with their trusted adult and the ability to assign a trusted adult to view a part of the record. Discussion: By directly involving youth in the design of the PHR, we are able to ensure we included the necessary health and life skills elements that they require. As a PHR is created for foster youth, it is important to consider the multiple uses that the data may have for emancipated youth. Conclusion: A PHR for foster youth needs to include an appropriate combination of information and education for a vulnerable population. In addition to providing some of their basic health and custody information, a PHR provides an opportunity to give them information that can be trusted to explain common diagnoses, medications, and family health history risks.